STUDY OF THE COAGULATION OF COLLOIDAL SYSTEM OF Fe(OH)3 BY INFLUENCE OF TARA GUM - Tapia H., N. (2010)
It has been studied the influence of the concentration and the pH of solution of tara gum in the coagulation of colloidal system of Fe(OH)3 with positive colloidal particles. The experimental data show that the coagulation is better for 0,1 g/75 ml solution of tara gum and the optimum pH is 5. The kinetic of coagulation was fast and finished after 5 minute.